Down-converters with doped solid solution crystals GaSe1-xSx for THz spectrometry - Huang, Zhiming; Huang, Jingguo; Gao, Yanqing; Yang, Q.-J; Andreev, Yury M. 1946-; Kokh, Konstantin A.; Lanskii, Grigory V.; Lisenko, A. A.; Svetlichnyi, Valerii A. (Proceedings of SPIE)
We launched into a development of a new stand-off sensing system that can detect atmospheric and hazardous gases in real atmosphere utilizing THz technology. Narrow line width, <0.1 cm-1, long-wave (mid-IR and THz) source based on difference frequency generation (DFG) in collinear configuration in GaSe0.91S0.09:Al(0.03 at. %) using seeded YAG laser and KTP OPO as pump sources was designed. The low optical loss coefficient and large hardness, together with the simplicity of the processing, make GaSe0.91S0.09:Al(0.03 at. %) as a high-reliable and effective THz-wave generator suitable for out-of-door application. We demonstrate incoherent terahertz wave detection by stand-off room temperature Schottky diodes located at over 110 m using open waveguide formed by multitude HPE lenses, mirrors and/or unpolished reflectors.